Understanding your gifted child from the inside out a guide to the social and emotional lives of gifted kids - Delisle, James R., 1953- (Waco, Texas : Prufrock Press Inc., 2018)
Understanding Your Gifted Child From the Inside Out provides an engaging and encouraging look at raising gifted children today. A follow-up to the best-selling "Parenting Gifted Kids: Tips for Raising Happy and Successful Children," this new edition focuses on the social and emotional aspects of giftedness, highlighting new information on the issues of perfectionism, self-advocacy, underachievement, mindfulness, and the impact of technology on gifted kids' relationships. The book also features a section on life beyond college, for those readers whose children are no longer children. Understanding Your Gifted Child From the Inside Out features real-life stories about the lives of gifted children and how they and their parents recognize and enjoy the many intellectual talents and social and emotional insights they possess.
Introduction -- Understand what giftedness is . . . and what it is not -- Know the distinction between "better at" and "better than" -- Stop paying interest on a bill you never owed -- Your gifted child's education: getting it right -- Appreciate that less than perfect is more than acceptable -- Living the nuanced life -- Deep roots, long branches: using the past to understand the present -- Write your dreams in pencil -- Make a life, not just a living -- Life is not a race to see who can get to the end the fastest -- References -- Resources -- About the author.
Revised edition of the author's Parenting gifted kids, c2006.
Includes bibliographical references (pages 193-197).
108504
Keywords: Parents of gifted children; Parenting; Gifted children -- Education; Education -- Parent participation